The relationship of compliance with a low purine diet with recursion of gout athritis disease in the elderly in the working area of the Banda Sakti health center Lhokseumawe city - Hernita, Hernita; Cut Linar (Sean Institute, 2024)
According to WHO, the incidence of gouty arthritis has increased by around 1.2% over the last 20 years. The prevalence in the last 5 years is estimated at 2.69%, rising to as high as 25% among the elderly of the world's population who have been attacked by gout (Gouty arthritis), where 5-10% are those aged 5-20 years and 20% are those aged over 55 year. The aim of this study was to identify the relationship between low diet adherence and recurrence of gouty arthritis in the elderly in the Banda Sakti Health Center area, Lhokseumawe City. The research was conducted on August 1, 2023. This research is correlational in nature. The research population was 58 respondents. The sampling technique used a total population of 58 respondents. Data collection by distributing questionnaires. Next, the data is processed with the help of a computerized system through the stages of editing, scoring, tabulating, coding, processing and cleaning. The results of the study showed that compliance with a low purine diet in the Banda Sakti Health Center Working Area, Lhokseumawe City was in the compliant category, namely 35 respondents (60.3%). Recurrence of Gout Athritis in the Banda Sakti Health Center Working Area, Lhokseumawe City was in the non-recurrence category, namely 31 respondents (53.4%). Meanwhile, statistical analysis using the Chi Square test shows that the p value = 0.000 < α = 0.05, so Ha is accepted and Ho is rejected, which means there is a relationship between adherence to a low purine diet and recurrence of gouty arthritis in the elderly in the Banda Sakti Health Center area, Lhokseumawe City. It is hoped that the elderly can increase their compliance regarding low-purine diet compliance with recurrence of gouty arthritis in the elderly.